Community Empowerment Training in Utilizing Catfish Processing Waste to Enhance Product Value - Nurmalasari Yanti; Ruly Awidiyantini (Jurnal Pengabdian Masyarakat Al-Fatimah, 2025)
Pademawu Timur Village, located in Pademawu District, Pamekasan Regency, has abundant natural resources, including rice, tobacco, bananas, and peanuts, making agriculture the primary livelihood for most residents. Additionally, this village is known as the largest catfish producer in Pamekasan, where residents cultivate catfish that are processed into various products. However, waste such as fish bones and heads are still discarded. This study aims to identify ways to utilize processed catfish waste to create value-added products. The research method involves providing training to the local community on techniques for processing catfish waste into economically valuable products. The results indicate that the community is capable of processing catfish waste into products that can increase their income, such as catfish crackers and animal feed. The contribution of this study is to provide solutions for processing catfish waste that benefit the economic well-being of the residents of Pademawu Timur Village